(3GdCQLhRI GdefHgI Ydi CSeGA GdbQGA hGdQhGI hCUhd GdbQGBJs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj, J (B444 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdaQO Cgd GdeYGdi hGdSfG hGdeLO Pi GdaVd hGdGfYGe hGdGMSGf QH GdYHGO GdSjO GdefGf s
(3BNQgG (B:s
(3hGSJQ YjhHi hGZJaQ RdGJi hGZaQ PfhHkG gi ef gfGJi s
(3PcQ ajgG GdCFeI GdbQGAs
(3hgj HQhGjI CHj YHO Gddg eMeO Hf YjSi GdCfUGQi GdCfOdSi Yf GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B407 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B10 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs